2023
DOI: 10.1007/s11135-022-01601-8
|View full text |Cite
|
Sign up to set email alerts
|

Is there a growing use of mobile devices in web surveys? Evidence from 128 web surveys in Germany

Abstract: Recent advances in web survey methodology were motivated by the observation that respondents increasingly use mobile devices, such as smartphones and tablets, to participate in web surveys. Even though we do not doubt this general observation, we argue that the claim is lacking a solid empirical basis. Most research on increasing mobile device use in web surveys covers limited periods of time and/or analyzes data from only one study or panel. There is a surprising lack of comprehensive overviews on the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The study was designed to collect cursor-based interactions, leaving out participants using mobile devices and touchscreens (tablets, etc.). Considering the increasing prevalence of mobile device usage (Gummer et al, 2023), this exclusion might have limited the generalizability of the findings. Nevertheless, because the survey layout is typically very different on mobile devices than on computers, this topic calls for a separate study.…”
Section: Limitationsmentioning
confidence: 99%
“…The study was designed to collect cursor-based interactions, leaving out participants using mobile devices and touchscreens (tablets, etc.). Considering the increasing prevalence of mobile device usage (Gummer et al, 2023), this exclusion might have limited the generalizability of the findings. Nevertheless, because the survey layout is typically very different on mobile devices than on computers, this topic calls for a separate study.…”
Section: Limitationsmentioning
confidence: 99%
“…Much of the research on effects of survey length predates the widespread use of online surveys as well as general access to internet on mobile devices. Many people now use mobile devices to complete surveys: one study found that between 25.1% and 39.0% completed their web survey using a smartphone during the 2020 wave of data collection, which was up from 2.7%-6.3% during the 2012 wave (Gummer et al, 2023). For these reasons, it is necessary to replicate and extend this research to determine whether these findings hold in the current context.…”
Section: Order Effects In Job Analysis Survey Datamentioning
confidence: 99%
“…In the May 2022 wave of the German Internet Panel, 56% of respondents participated with a computer, 4% with a tablet, and 40% with a smartphone. 2 This overall trend is supported by a variety of national and international studies (see, for example, Gummer et al, 2019, 2023; Peterson et al, 2017; Revilla et al, 2016) and enables researchers to consider new communication forms in web surveys.…”
Section: Introduction and Research Questionsmentioning
confidence: 96%